Hymenobacter armeniacus sp. nov. and Hymenobacter montanus sp. nov., two radiation-resistant bacteria from soil. Issue 3 (1st March 2022) - Park, Yuna; Chang, Yoonjee; Kim, Myung Kyum
Abstract : Two bacterial strains, designated BT189 T and BT664 T, were isolated from soil sampled in the Republic of Korea. Phylogenetic analysis based on the 16S rRNA gene sequences showed that strains BT189 T and BT664 T belonged to the genus Hymenobacter, family Hymenobacteraceae (order Cytophagales ). The 16S rRNA genes of the two strains shared a sequence similarity of 93.7 %. The closely related species of strain BT189 T were Hymenobacter rubidus DG7B T (97.1 % 16S rRNA similarity) and Hymenobacter terrae DG7A T (96.7 %). The closest related species to strain BT664 T were Hymenobacter sedentarius DG5B T (95.3 %) and Hymenobacter terrenus MIMtkLc17 T (95.2 %). The genome sizes of strains BT189 T and BT664 T were 5 285 287 and 5 475 357 bp, respectively. The genomic DNA G+C contents of strains BT189 T and BT664 T were 63.2 and 59.3 mol%, respectively. The main fatty acids of strain BT189 T were iso-C15 : 0, anteiso-C15 : 0 and summed feature 3 (C16 : 1  ω 6 c /C16 : 1  ω 7 c ), and those of strain BT664 T were iso-C15 : 0, C16 : 1  ω 5 c and summed feature 3 (C16 : 1  ω 6 c /C16 : 1   ω 7 c ). The main polar lipid in both strains was phosphatidylethanolamine and the predominant respiratory quinone was MK-7, supporting the affiliation of these strains with the genus Hymenobacter . Based on the results of biochemical, chemotaxonomic and phylogenetic analyses, two novel species, Hymenobacter armeniacus BT189 T (=KCTC 72341 T =NBRC 114843 T ) and Hymenobacter montanus BT664 T (KACC 21967 T =NBRC 114856 T ), are proposed.